Liver cancers with stem/progenitor-cell features: a rare chemotherapy-sensitive malignancy - Köhler, Bruno Christian; Waldburger, Nina; Schlamp, Kai; Jäger, Dirk; Weiss, Karl Heinz; Schirmacher, Peter; Springfeld, Christoph (OncoTarget, 2017)
Primary liver tumors are a heterogeneous group of malignancies. Besides classical hepatocellular carcinoma (HCC) and cholangiocarcinoma (CC), combined and intermediate forms of liver cancer exist and can express stem-cell markers like nuclear cell adhesion molecule (NCAM-1/CD56), c-kit (CD117) or epithelial cell adhesion molecule (EpCAM) together with high proliferative activity. Liver tumors with progenitor-cell features are associated with an unfavorable prognosis, but the phenotype has not resulted in therapeutic consequences so far., We report three patients with liver cancers with stem/progenitor-cell features that responded exceptionally well to chemotherapy. These encouraging results indicate that the identification of liver cancer with stem/progenitor-cell phenotype in a patient´s tumor might justify an attempt to treat the patient with chemotherapy. Further case studies and finally clinical trials will be necessary to determine the optimal treatment for patients with this rare form of liver cancer.
Gesehen am 09.10.2018